An evaluation of the physical plant of the U.P. College of Education - Encisa, Aurora (Ricacho) ([Quezon City s.n.], 1974)
The facilities and services of the College were analyzed in terms of adequacy, manner of utilization, management and quality and efficiency of maintenance functions. The current degree programs and on-going projects offered and undertaken by the nine departments require additional facilities and equipment. The maintenance and upkeep of the physical plant, at present satisfactory, nevertheless needs vigorous and more dedicated concern of personnel in order to attain excellence.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Philippines. University -- College of Education